THEORETICAL FOUNDATIONS OF ACCOUNTING FOR FINANCIAL ANALYSIS AND AUDITING OF PUBLIC-PRIVATE PARTNERSHIP ENTITIES - Razzakov Durbek , Khashimovich (THE INNOVATION ECONOMY, 2025)
This article examines the theoretical foundations of accounting, financial analysis, and auditing of entities operating under public-private partnerships (PPPs) in Uzbekistan. It analyzes the core principles of accounting, methods of financial analysis, and audit procedures applied in PPP enterprises. A mixed-methods approach was employed, combining qualitative analysis of legislation and enterprise reports with quantitative analysis of financial indicators. The findings indicate that modern accounting and auditing methods enhance financial transparency, though challenges related to data quality and professional qualifications persist. Recommendations based on international experience are tailored to Uzbekistan’s context.